ASSESSMENT OF AIRBORNE PARTICULATE MATTER (PM2.5) IN UNIVERSITY CLASSROOMS OF VARRYING OCCUPANCY - K. Aziz; Z. Ali; Z. A. Nasir; I. Colbeck (Journal of Animal and Plant Sciences, 2015)
Air pollution is a major concern in Pakistan. Levels of particulate matter (PM ) in educational built environments, have 2.5 not yet been studied comprehensively in Pakistan. This study was conducted to assess relationships between indoor and outdoor particulate matter in classrooms of the University of the Punjab, Lahore, using a DUSTTRAK Aerosol Monitor (TSI Model 8520). Sampling for PM concentrations was carried out simultaneously outdoors and indoors in different 2.5 classrooms on the campus. According to the level of occupancy three classrooms were selected i.e. Classroom I: low occupancy, Classroom II: medium occupancy and Classroom III: high occupancy. Simultaneous outdoor measurements were carried out at rooftop of each classroom. A tracer method was used to measure the air change per hour in each classroom. The 24 hour average concentrations of PM in Classrooms I, II and III were observed to be 282 μg/m3, 75 2.5 μg/m3 and 673 μg/m3 whereas 24 hour average outdoor levels were 324 μg/m3, 121 μg/m3 and 998μg/m3 respectively. Results showed a significant impact of ambient air and occupancy level on PM levels inside classrooms and all 2.5 observed values exceeded the WHO limits. 2.5 knowledge on levels of exposure to air pollutants in
Keywords: Particulate Matter; PM; Classrooms.